233 Mechanical Ventilation-Induced Apoptosis in Newborn Rat Lung is Mediated Via Fasl/Fas Pathway. (October 2012) - Kroon, A; Riccio, V Del; Tseu, I; Huang, Z; Wang, J; Post, M
Abstract : Rationale: Mechanical ventilation induces pulmonary apoptosis and inhibits alveolar development in preterm infants, but the molecular basis for this apoptotic injury is unknown. Objective: To determine the signaling mechanism(s) of ventilation(stretch)-induced apoptosis in newborn rat lung. Methods: Seven-day old rats were ventilated with room air for 24 h using moderate tidal volumes (8.5 mL.kg -1 ). Isolated fetal rat lung epithelial and fibroblast cells were subjected to continuous cyclic stretch (5, 10 or 17% elongation) for up to 12 h. Measurements and main results: Prolonged ventilation increased significantly the number of apoptotic alveolar type II cells (i.e. TUNEL-labelling, anti-cleaved caspase-3 immunochemistry) and was associated with increased expression of the apoptotic mediator Fas Ligand (FasL). Fetal lung epithelial cells, but not fibroblasts, subjected to maximal (i.e. 17%, but not lesser elongation) cyclic stretch exhibited increased apoptosis (i.e. nuclear fragmentation; DNA laddering) which appeared to be mediated via the extrinsic pathway (increased expression of FasL and cleaved caspase-3, -7 and -8). The intrinsic pathway appeared not to be involved (minimal mitochondrial membrane depolarization (i.e. JC-1 flow analysis); no activation of caspase-9). Universal caspases inhibition and neutralization of FasL abrogated the stretch-induced apoptosis. Conclusion: Prolonged mechanical ventilation induces apoptosis of alveolar type II cells in newborn rats and the cellular mechanism involves activation of the extrinsic death pathway via the FasL/Fas system.